Change of identity: the psychological and emotional impact of caring for someone with multiple sclerosis - Heward, K.; Gough, B.; Molineux, Matthew (Pier Professional Ltd, 2011)
The diagnosis of a chronic progressive condition such as multiple sclerosis (MS) can impact on many aspects of daily life. Living with, and caring for, an individual with such a condition is likely to have emotional and psychological consequences. We carried out semi-structured interviews with nine partners and analysed the interview transcripts using grounded theory (Strauss & Corbin, 1998), the phase presented in this article formed part of a larger overall study that explored the impact of living with MS for partners and a family. Our analysis in this phase highlights two core themes centred on identity issues faced by the participants: ‘playing detective’ in order to acquire information and manage the situation; and ‘reshaping identities’ in a shifting context, which reflected the participants' difficulties in reconfiguring important identities (at work and at home). Although previous research has addressed how carers cope, there is a dearth of qualitative literature relating to whether or not partners' identities are affected by taking a central role in caring, including how previous identities are maintained and new ones acquired.